A Universal Perovskite Nanocrystal Ink for High‐Performance Optoelectronic Devices. Issue 8 (25th December 2022) - Song, Hochan; Yang, Jonghee; Jeong, Woo Hyeon; Lee, Jeongjae; Lee, Tack Ho; Yoon, Jung Won; Lee, Hajin; Ramadan, Alexandra J.; Oliver, Robert D. J.; Cho, Seong Chan; Lim, Seul Gi; Jang, Ji Won; et al.
Abstract: Semiconducting lead halide perovskite nanocrystals (PNCs) are regarded as promising candidates for next‐generation optoelectronic devices due to their solution processability and outstanding optoelectronic properties. While the field of light‐emitting diodes (LEDs) and photovoltaics (PVs), two prime examples of optoelectronic devices, has recently seen a multitude of efforts toward high‐performance PNC‐based devices, realizing both devices with high efficiencies and stabilities through a single PNC processing strategy has remained a challenge.  In this work, diphenylpropylammonium (DPAI) surface ligands, found through a judicious ab‐initio‐based ligand search, are shown to provide a solution to this problem. The universal PNC ink with DPAI ligands presented here, prepared through a solution‐phase ligand‐exchange process, simultaneously allows single‐step processed LED and PV devices with peak electroluminescence external quantum efficiency of 17.00% and power conversion efficiency of 14.92% (stabilized output 14.00%), respectively. It is revealed that a careful design of the aromatic rings such as in DPAI is the decisive factor in bestowing such high performances, ease of solution processing, and improved phase stability up to 120 days. This work illustrates the power of ligand design in producing PNC ink formulations for high‐throughput production of optoelectronic devices; it also paves a path for "dual‐mode" devices with both PV and LED functionalities. Abstract : A functional CsPbI3  perovskite nanocrystal ink is developed through solution‐phase ligand exchange with 3, 3‐diphenylpropylammonium iodide, attributed to singular stabilization by diphenyl group and rigorous surface passivation. This enables a "universal" demonstration of high‐performance photovoltaics and light‐emitting devices while ensuring excellent phase stability and device longevity.